Analysing Word-Formation Processes of Complex Words in Folk Poems and Songs in Kalhori Kurdish Language: Based on Samples form Analysing Ganjinehay-e Bar Bad-e Yad - vahid sajjadifa; Nastaran Kasani (پژوهشنامه ادبیات کردی, 2024)
Kalehri Kurdish folk poems are among the valuable parts of the folk literature of Kurdish-speaking people in different regions of Kermanshah and Ilam. In these poems, many words have complex structures based on various lexical and musical considerations, and they are coined through different word formation processes that can be either hierarchical (step by step) or non-hierarchical (instantaneous), and undoubtedly each of these words has a particular part of speech. The study of complex word structures in these poems, from the mentioned perspectives, can provide a clear understanding of the word formation process in them. In this research, relying on descriptive-comparative and case study methods, efforts have been made to examine the word formation process, grammatical categories, and hierarchical and non-hierarchical nature of words used in Kalehri Kurdish folk poems, collected in the book Ganjinehay-e Bar Bad-e Yad by Ibrahim Rahimi Zanganeh and colleagues, based on the thirteen word formation processes of Shaghaghi (2007). The findings of this research indicate that the word formation process in complex words of these poems is carried out through five word formation processes: combination, derivation, combination-derivation, repetition, and truncation, which have grammatical categories of the noun, adjective, adverb, and infinitive, and the word formation process is hierarchical in all cases.